The Qur'an, morality and critical reason : the essential Muhammad Shahrur - Shaḥrūr, Muḥammad. (Social, Economic and Political Studies of the Middle East and Asia, 2009)
This book presents the work and ideas of the Syrian writer Muhammad Shahrur to the English-speaking world. Shahrur is at the moment the most innovative intellectual thinker in the Arab Middle East. Often described as the 'Martin Luther of Islam,' he offers a liberal, progressive reading of Islam that aims to counter the influences of religious fundamentalism and radical politics. Shahrur's innovative interpretation of the Qur'an offers groundbreaking new ideas, based on his conviction that centuries of historical Islam, including scholarship in the traditional Islamic religious sciences, have obscured or even obliterated the Qur'an's progressive and revolutionary message. That message is one that has endured through each period of human history in which Islam has existed, encouraging Muslims to apply the most contemporary perspective available to interpret the Qur'an's meaning.